2020
DOI: 10.1158/1535-7163.mct-19-1004
|View full text |Cite
|
Sign up to set email alerts
|

ARX788, a Site-specific Anti-HER2 Antibody–Drug Conjugate, Demonstrates Potent and Selective Activity in HER2-low and T-DM1–resistant Breast and Gastric Cancers

Abstract: First-generation antibody-drug conjugates (ADC) are heterogeneous mixtures that have shown clinical benefit, but generally exhibited safety issues and a narrow therapeutic window due, in part, to off-target toxicity caused by ADC instability. ARX788 is a next-generation, site-specific anti-HER2 ADC that utilizes a unique nonnatural amino acid-enabled conjugation technology and a noncleavable Amberstatin (AS269) drug-linker to generate a homogeneous ADC with a drug-to-antibody ratio of 1.9. ARX788 exhibits high… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(85 citation statements)
references
References 40 publications
0
85
0
Order By: Relevance
“…ARX788 is a site-specific ADC that consists of an anti-HER2 antibody linked to a highly potent tubulin inhibitor AS269, using a unique non-natural amino acid-enabled conjugation technology and a non-cleavable linker [ 25 ]. First results from a phase 1 trial showed antitumor activity in HER2-positive BC leading to a fast track designation granted by the FDA in January 2021 [ 26 ].…”
Section: Adcs Under Investigationmentioning
confidence: 99%
“…ARX788 is a site-specific ADC that consists of an anti-HER2 antibody linked to a highly potent tubulin inhibitor AS269, using a unique non-natural amino acid-enabled conjugation technology and a non-cleavable linker [ 25 ]. First results from a phase 1 trial showed antitumor activity in HER2-positive BC leading to a fast track designation granted by the FDA in January 2021 [ 26 ].…”
Section: Adcs Under Investigationmentioning
confidence: 99%
“…91 Currently, several HER2-directed ADCs are under clinical investigation for both HER2 amplified and HER2 expressing but not amplified BCs, including ARX788 and XMT-1522.ARX788, a novel next-generation anti-HER2 ADC containing an anti-HER2 monoclonal antibody sitespecifically conjugated to amberstatin, 92,93 has shown antitumor effects and rapid tumor regression in murine xenograft models of the HER2+ BC cell lines BT474 and HCC1954. 92 Furthermore, ARX788 showed a stronger inhibitory effect than T-DM1 on T-DM1-responsive BC cells and caused complete tumor regression in a trastuzumab-resistant BC xenograft model derived from JIMT-1 cells. 94 Two Phase 1 trials on of ARX-788 (clinicaltrials.gov identifiers: NCT02512237 and NCT03255070) are ongoing but the results have not yet been published.…”
Section: Adcsmentioning
confidence: 99%
“…To overcome this limitation, non-natural amino acids were incorporated into the recombinantly expressed antibody. An example is ARX788, in which a cytotoxic payload is conjugated to the non-canonical amino acid (para-acetyl phenylalanine) in the heavy chain at a predetermined site [ 67 ].…”
Section: Breast Cancermentioning
confidence: 99%